INFLUENCE OF VARIOUS MECHANICAL IMPURITIES IN TRANSFORMER OILS ON ELECTRIC AND MAGNETIC FIELDS - Avazov, Bobomurod; Yusupov , Dilmurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: The article presents an analysis of the influence of various mechanical impurities of transformer oils on electric and magnetic fields based on scientific literature. The analysis showed that mechanical impurities contained in transformer oil affect the electric field. However, the influence of sludge, fibers and metal particles on the magnetic field is stronger. At the same time, the electromagnetic field is influenced by such types of mechanical impurities contained in transformer oil as asphalt deposits, fibers, soap compounds and metal particles.